UPAYA MEMINIMUMKAN AGENCY PROBLEM DENGAN MENGGUNAKAN KONSEP ISLAM TENTANG PERUSAHAAN - Moh Khoiruddin (Program Studi Manajemen, 2017)
Although companies generally have goals, in company management practices, conflicts often arise between shareholders as stakeholders and managers, and / or between shareholders and creditors. Agency problems can be experienced by companies that are operationalized with conventional concepts or those based on sharia. Conventionally, agency problem solutions can only be approached with material or incentive-oriented approaches. From the results of a number of studies, it is concluded that an incentive approach alone does not significantly reduce agency problems in the company. In the sharia concept, the anticipation process for agency problems is carried out from the start of an agreed business contract on the basis of mutual trust and trust. The approach used is not only material but also immaterial, which is oriented towards the afterlife. The moral hazard control system does not only arise from the rules made but also inherently from all parties who agree to the contract. It is possible to achieve higher supervisory cost efficiency in theory with this sharia concept.